Revived is the Lord --- - Hochradner, Thomas (Muzikološki zbornik, 2014)
To envision the non-presentable is a venture. This will only succeed if a conventional frame is going to secure the intention, if the composer is able to release extraordinary creative potential and the audience is endowed with effectual imagination. A comparison of Georg Friedrich Handel's early oratorio La Resurrezione HWV 47 (1708) and Franco Alfano's opera Risurrezione, premiered 1904, which is based on a libretto by Cesare Hanau after Lev Tolstoy's novel Resurrection, makes it clear that certain structures - of the works' dispositions as well as the musical realizations help to avoid any danger of irrelevance or chauvinism. Whereas Handel's approach is a sacral, Alfano's a secular one, both times a starting position for the composer arises which basically incites a link between the antithetic spheres. Further on not similarities, but possibilities to individualize a topic are questioned, a topic which - notwithstanding the attraction of characterizing a transcendental area compositionally - has scarcely been taken up in the course of music history.
Keywords: Alfano, Franco, 1875-1954; dramatični pristop; dramatizacija sakralnosti; glasba; Händel, Georg Friedrich, 1685-1759; La Resurrezione; music; Risurrezione; vzorci dramatizacije sakralnosti